Real Effective Exchange Rate Determination in Indonesia: A Behavioral Equilibrium Exchange Rate Approach - Didi Nuryadin (Universitas Islam Indonesia, 2006)
The aim of this paper is to analyze the determination of real effective exchange rate in Indonesia for the period 1994.1-2004.6 using behavioral approach. The sets of funda¬mental variables consisting of net foreign asset, term of trade, ratio total trade to GDP, pri¬vate and government consumption were used to estimate for resulting estimation of behav¬ioral real effective exchange rate.The data was used in this study using time series monthly data from 1994.1 – 2004.6. The source of data were taken from International Financial Statistic and Central Bank of Indonesia. The method of analysis is multivariate cointegration methods of Johansen to determine the long run relationship real effective exchange rate. Exchange rate misalign¬ment was also used in this study by plotting the series between actual real effective exchange rate and the behavioral equilibrium exchange rate. The results of this study showed that from the estimation result of behavioral equi¬librium exchange rate, some variables of the sets fundamental variables such as net foreign asset, term of trade and ratio total trade to GDP were correctly signed, plausible magnitude and statistically significant. But, government and private consumption were not statistically significant and incorrectly signed. From the plotted result between actual and equilibrium estimation, it represents that for the period post-1997, the currency has been undervalued. The close alignment between actual and equilibrium was occurred in 1998 and 1999. But at the end of the sample, the currency looked overvalued.Keywords: Real effective exchange rate, Behavioral equilibrium approach, Cointegration